Beyond mineral metabolism, is there an interplay between FGF23 and vitamin D in innate immunity? - Bacchetta, Justine (Pediatr Nephrol, 2012)
Fibroblast Growth Factor 23 (FGF23) is an ‘endocrine’ FGF acting in the kidney as a phosphaturic hormone and a suppressor of active vitamin D, through an inhibition of the 1α hydroxylase and a stimulation of the 24 hydroxylase. Beyond its well-known effects on the bone/kidney/parathyroid axis and its deregulation during chronic kidney disease (CKD), recent evidence has revealed its direct systemic effects on cardiovascular health. In the meantime, studies have highlighted health implications for vitamin D inside and outside CKD that also extend beyond its classical actions on mineral homeostasis and bone metabolism: vitamin D has indeed been shown to exert pluripotent non-classical effects as a modulator of immune function in monocytes, mainly through the stimulation of the antimicrobial cathelicidin. The aim of this review is to provide new insights on the interplay between FGF23 and vitamin D in innate immunity in the context of CKD.